Rare example of TICT based optical responses for the specific recognition of Cr3+ by a 2,2?:6?,2?-terpyridine derivative and demonstration of multiple logic operations - Mahato, Prasenjit; Saha, Sukdeb; Das, Amitava (Journal of Physical Chemistry C, 2012)
Chemosensor L showed a nonlinear fluorescence response on specific binding to Cr3+ ion in the presence of various alkali, alkaline-earth, transition, and lanthanide metal ions. A luminescence band with maxima at 512 nm for L was observed (λext = 330 nm) for a twisted intramolecular charge transfer (TICT) transition following antienergy gap law behavior. However, normal energy gap law behavior prevailed on formation of a new nonluminescent charge transfer complex, Mn+·L. For paramagnetic metal ions, paramagnetism induced luminescence quenching could have also contributed to this. A new switched on fluorescence response at λems of 356 nm (λext of 330 nm) was observed due to Franck–Condon charge transfer (FC-CT) transition only on the formation of a complex, (Cr3+)2·L. Spectral studies revealed a unique dynamic coordination behavior and migration of Cr3+ from the terpyridyl fragment to the NNMe2 center of L as a function of the varying concentration of another ion (Zn2+) and the subtle difference in the binding affinities of the terpyridyl moiety toward Cr3+ and Zn2+. Further, spectral responses of L toward Zn2+, different concentration of Cr3+, H+ and on subsequent addition of F– as different ionic inputs could be correlated well for demonstrating various basic and combinatorial circuits.

Ratiometric detection of Cr3+ and Hg2+ by a naphthalimide-rhodamine based fluorescent probe - Mahato, Prasenjit; Saha, Sukdeb; Suresh, E.; Liddo, Rosa Di; Parnigotto, Pier Paolo; Conconi, Maria Teresa; Kesharwani, Manoj K.; Ganguly, Bishwajit; Das, Amitava (Inorganic Chemistry, 2012)
Newly synthesized rhodamine derivatives, L1 and L2, are found to bind specifically to Hg2+ or Cr3+ in presence of large excess of other competing ions with associated changes in their optical and fluorescence spectral behavior. These spectral changes are significant enough in the visible region of the spectrum and thus, allow the visual detection. For L1, the detection limit is even lower than the permissible [Cr3+] or [Hg2+] in drinking water as per standard U.S. EPA norms; while the receptor, L2 could be used as a ratiometric sensor for detection of Cr3+ and Hg2+ based on the resonance energy transfer (RET) process involving the donor naphthalimide and the acceptor Cr3+/Hg2+-bound xanthene fragment. Studies reveal that these two reagents could be used for recognition and sensing of Hg2+/Cr3+. Further, confocal laser microscopic studies confirmed that the reagent L2 could also be used as an imaging probe for detection of uptake of these ions in A431 cells.

Recognition of Hg 2+ and Cr 3+ in physiological conditions by a rhodamine derivative and its application as a reagent for cell-imaging studies - Saha, Sukdeb; Mahato, Prasenjit; Reddy, Upendar G.; Suresh, E.; Chakrabarty, Arindam; Baidya, Mithu; Ghosh, Sudip K.; Das, Amitava (Inorganic Chemistry, 2012)
A new rhodamine-based receptor, derivatized with an additional fluorophore (quinoline), was synthesized for selective recognition of Hg2+ and Cr3+ in an acetonitrile/HEPES buffer medium of pH 7.3. This reagent could be used as a dual probe and allowed detection of these two ions by monitoring changes in absorption and the fluorescence spectral pattern. In both instances, the extent of the changes was significant enough to allow visual detection. More importantly, the receptor molecule could be used as an imaging reagent for detection of Hg2+ and Cr3+ uptake in live human cancer cells (MCF7) using laser confocal microscopic studies. Unlike Hg(ClO4)2 or Hg(NO3)2 salts, HgCl2 or HgI2 failed to induce any visually detectable change in color or fluorescence upon interaction with L1 under identical experimental conditions. Presumably, the higher covalent nature of HgII in HgCl2 or HgI2 accounts for its lower acidity and its inability to open up the spirolactam ring of the reagent L1. The issue has been addressed on the basis of the single-crystal X-ray structures of L1·HgX2 (X– = Cl– or I–) and results from other spectral studies.

Rhodamine-alginate conjugate as self-indicating gel beads for efficient detection and scavenging of Hg 2+ and Cr 3+ in aqueous media - Saha, Sukdeb; Chhatbar, Mahesh U.; Mahato, Prasenjit; Praveen, L.; Siddhanta, A. K.; Das, Amitava (Chemical Communications, 2012)
Effective extraction of Hg2+ and Cr3+ ions from aqueous media by novel rhodamine–alginate polymer-based highly fluorogenic, as well as colorimetric, chemosensor beads.

Rapid conductometric sensor for the analysis of cyanide using imidazole based receptor - Paul, Anirban; Perween, Mosarrat; Saha, Sukdeb; Srivastava, Divesh N.; Das, Amitava (Physical Chemistry Chemical Physics, 2015)
A specific and efficient hydrogen bonding interaction between cyanide and the HN-H [imidazole] in an aqueous medium has been utilized for the selective recognition of cyanide under physiological conditions. The possibility of utilizing such an interaction for developing any practical device for the specific detection of cyanide in an aqueous environment has not been explored to date. We now report a simple dip and read conductometric sensor for cyanide ions using a tailored electrode in aqueous media. The purpose built reagent, 2-phenyl-1H-anthra-[2,3-d]-immidazole-5,10 dione was immobilized in a polyaniline matrix to fabricate this conductometric device. The homogeneous immobilization of the receptor in polyaniline was confirmed by FT-IR mapping. The proposed transduction mechanism is charge neutralization on the polyaniline moiety, which ultimately inhibits the protonation resulting in a decrease in the conductance of polyaniline. The sensor response was measured in three ranges of cyanide concentration (10(-10) M to 10(-8) M; 10(-8) M to 10(-6) M and 10(-6) M to 10(-3) M). Whereas the device is found insensitive in the first range, it acts as a detector in the second range and as a proportional sensor in the third range. The minimum detection limit of this device was found to be 10 nmol L-1 (2.6 ppt), which is significantly less than the WHO guideline values. The responses have been investigated under various conditions such as different pH and the electrochemical state of the polymer. The current device has been found to be better close to neutral pH and at a 400 mV vs. Ag/AgCl potential. The reproducibility and repeatability of the sensor was investigated and interference studies were performed.